2017
DOI: 10.20944/preprints201705.0057.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Thermal Conductivities of Periodic Fibrous Composites as Defined by a Mathematical Model

Abstract: Abstract:In this paper, a geometric body-centered model to simulate the periodic structure of unidirectional fibrous composites is presented. To this end, three prescribed configurations are introduced to predict in a deterministic manner the arrangement of internal and neighboring fibers inside the matrix. Thus, three different representative volume elements (RVEs) are established. Furthermore, the concept of the interphase has been taken into account, stating that each individual fiber is encircled by a thin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The heat flow across intermittent paths between the conducting filler network is mainly determined by the wt% of the two fillers, their orientation angles, and the interactions between the two fillers and their influences on the adhesion between glass fibers and the epoxy matrix. Based on finite element analysis‐based simulation, [ 34,35 ] it is reported that the random orientation of MWCNT will negatively impact the thermal conductivity, more than that of GNP. Hence, it is critical to fix the wt% of MWCNT and then determine the matching wt% of GNP for optimizing the thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…The heat flow across intermittent paths between the conducting filler network is mainly determined by the wt% of the two fillers, their orientation angles, and the interactions between the two fillers and their influences on the adhesion between glass fibers and the epoxy matrix. Based on finite element analysis‐based simulation, [ 34,35 ] it is reported that the random orientation of MWCNT will negatively impact the thermal conductivity, more than that of GNP. Hence, it is critical to fix the wt% of MWCNT and then determine the matching wt% of GNP for optimizing the thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%